Dynamic interaction of the monorail–bridge system using a combined finite element multibody-based model. (June 2015) - Naeimi, Meysam; Tatari, Meisam; Esmaeilzadeh, Amin; Mehrali, Mohammad
To assess the dynamic behavior of monorail–bridge system, an innovative model of train–guideway interaction has been developed based on multibody dynamics and finite element simulation. A finite element model of guideway structure for a particular monorail system is built up using parametric design language, considering a specific length of straddle monorail line in three dimensions. Both straight and curved track geometries are modeled to simulate the actual bridge infrastructure. Flexible elements are adopted for the guideway beams consisting of reinforced concrete profiles to increase the accuracy of the numerical simulations in a more realistic way. The bridge model indeed, is simulated using a beam-frame structure of composite steel–concrete material. A multibody simulation of monorail vehicle is then introduced using the commercial multibody software MSC Adams. The three-dimensional multibody model of the monorail vehicle together with the bridge subassemblies is eventually implemented in multibody environment. The entire dynamic model of the vehicle-track system consists of all flexible and rigid body elements. Dynamic responses of the vehicle and bridge system are then extracted for different loading conditions. The proposed numerical model is validated using some dynamic simulation results of the system from the vehicle manufacturer in the selected case study. The model is further verified against several analytical and measurement results reported in the literature both for straight and curved track configurations. The result of dynamic simulations gives an overview about the dynamic forces and reactions that can appear in bridge structure due to the train movement.